The Role of Auction Officials in Executing Intellectual Property Fiduciary Guarantees as Bank Credit Collateral - Rohman, Idris; Hafidz, Jawade (Jurnal Konstatering, 2026)
This study aims to determine the practice of notaries in Indonesia, namely the placement of the facer's fingerprints as authentic and vital evidence in various transactions, requiring adaptation to face the challenges of forgery and maintain validity. The placement of the facer's fingerprints emerged as a solution to increase security and legal certainty, using a normative juridical approach with a statutory approach method. Then, data was collected from primary legal materials (the Notary Law and related regulations), secondary (legal literature and journals), and tertiary (legal dictionaries and encyclopedias). Data collection methods included library studies, field observations, and interviews with competent sources. Data analysis used a qualitative descriptive-analytical method with a deductive-inductive thinking framework. The results show that the Notary Law requires the placement of fingerprints to increase the validity of deeds. Fingerprints, as unique biometrics, provide stronger legal certainty. However, its implementation faces technical challenges (system accuracy, infrastructure), legal (incomplete regulations, personal data protection), and social (public trust, digital literacy) challenges. Comprehensive and integrated regulations, which take into account technical, legal, and social aspects, are crucial to ensure the effectiveness, security, and fairness of the implementation of fingerprinting in the preparation of notarial deeds.